Update of Diagnostic and Treatment of Ludwig’s Angina - Ruíz Ramírez, Eliberto (2011)
Ludwig’s angina is a rapidly progressive cellulitis that involves sub mandibular, sub lingual and submental spaces bilaterrally. This was due mainly to per apical infections of the second and third mandible molars. Due to the rapid advancement of the clinical (which in certain occasions could even threaten the patient’s life) it is extremely important to know clearly the criteria for early diagnosis of Ludwig’s angina, which will enable us to provide the most appropriate treatment to halt the progress of the clinical and will prevent the onset of life-threatening complications.